Pengaruh Lokasi, Kelengkapan Produk, Dan Word Of Mouth Terhadap Keputusan Pembelian Pada Fajar Abadi Snack - Anugrah, Kamal Febrian (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The purpose of this research is to find out how location variables, product completeness, and oral conversation influence consumers' decisions to buy Fajar Abadi Snack products. Quantitative analysis techniques were then used using SPSS. The research population is unknown, so the sample is multiplied by 5 and there are 13 indicators. To distribute questionnaires, this research used a Likert scale questionnaire. Sample collection methods that do not rely on probability are used to collect samples. In cases where there is a connection with the research, the people who met the researcher are considered the sample. The SPSS test results show that the variables of location, product completeness, and word of mouth simultaneously influence the purchasing decision variable. Location has a significant effect on purchasing decisions with a sig value of 0.000 < 0.05, and product completeness has a significant effect on purchasing decisions with a sig value of 0.001 < 0.05. However, word of mouth does not have a significant effect on purchasing decisions with a sig value of 0.000 < 0.05. Â